2022
DOI: 10.7759/cureus.32519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Anticancer Activity of Blocking TNF Type 1 Receptors in Thioacetamide-Induced Hepatocellular Carcinoma in a Rat Model

Abstract: Background Hepatocellular carcinoma (HCC) can explicate about 90% of the total primary liver cancer cases, with approximately 800,000 new cases identified each year worldwide. In addition, any changes in the expression of the tumor necrosis factor α (TNF-α) type 1 receptor (TNFR1) might impact many biological processes, which may lead to cancer. Aims We conducted the following study to investigate the ability of CAY10500, a TNF-α inhibitor that prevents binding to the TNF recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There are only hints obtained from a recent mouse model of NASH-associated HCC that suggest that TNF-α neutralization may prevent anti-PD-1 exacerbation of HCC, which, however, warrants further mechanistic studies [16]. Previous preclinical studies testing anti-TNF agents in xenograft HCC [124] or chemically induced HCC mouse models [125], but not in obesity-or NASH-associated HCC mouse models, demonstrated that the blockade of TNF-α signaling hampered tumor progression by diminishing the expression of proinflammatory mediators within HCC tissue and promoting apoptosis in HCC cell. In addition, the combination of anti-TNF with 5-fluorouracil (FU), a classic chemotherapeutic agent, also inhibited tumor growth and improved survival of a mouse model of xenograft HCC [44].…”
Section: Treatment Considerations For Nafld-associated Hccmentioning
confidence: 99%
“…There are only hints obtained from a recent mouse model of NASH-associated HCC that suggest that TNF-α neutralization may prevent anti-PD-1 exacerbation of HCC, which, however, warrants further mechanistic studies [16]. Previous preclinical studies testing anti-TNF agents in xenograft HCC [124] or chemically induced HCC mouse models [125], but not in obesity-or NASH-associated HCC mouse models, demonstrated that the blockade of TNF-α signaling hampered tumor progression by diminishing the expression of proinflammatory mediators within HCC tissue and promoting apoptosis in HCC cell. In addition, the combination of anti-TNF with 5-fluorouracil (FU), a classic chemotherapeutic agent, also inhibited tumor growth and improved survival of a mouse model of xenograft HCC [44].…”
Section: Treatment Considerations For Nafld-associated Hccmentioning
confidence: 99%
“…It was also reported that, cycloastragenol suppressed the expression of SphK, MIP-1α, NF-κB, TNF-α, BAX, and cleaved caspase-3 in the UC rat model, associated with the overexpression of miR-143 and BCL2 (Bagalagel et al, 2022). Consequently, cycloastragenol could protect against UC by regulating SphK/MIP-1α/miR-143 axis, hence suppressing the inflammation and apoptosis-related signals (Bagalagel et al, 2022). miR-24 has been reported to be specifically upregulated in the colonic biopsies from patients with active UC, down-regulating the mRNA and protein expression of the tight junction-associated protein Cingulin and thus impairing the intestinal epithelial barrier formation (Soroosh et al, 2019).…”
Section: Micrornasmentioning
confidence: 86%
“…miR-141-3p is remarkably upregulated in the IECs of the mice model of UC and might affect the infiltration of inflammatory cells by targeting the chemokines CXCL9 or CXCL16 (Lee et al, 2015). It was also reported that, cycloastragenol suppressed the expression of SphK, MIP-1α, NF-κB, TNF-α, BAX, and cleaved caspase-3 in the UC rat model, associated with the overexpression of miR-143 and BCL2 (Bagalagel et al, 2022). Consequently, cycloastragenol could protect against UC by regulating SphK/MIP-1α/miR-143 axis, hence suppressing the inflammation and apoptosis-related signals (Bagalagel et al, 2022).…”
Section: Micrornasmentioning
confidence: 92%
“…The gene expression of Wnt, β-catenin, cadherin, SMAD4, and GAPDH mRNA levels in rat muscle lysate was performed as described previously by our group [7][8][9]. Table 1 shows the gene-specific PCR primers we used.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%